PEMBEKALAN TEKNIK ALGORITMA DALAM KEAMANAN DATA ERA REVOLUSI INDUSTRI 4.0 - Anwar, Nizirwan; Mulyani, Erry Yudhya; Ummanah, Ummanah (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Allah SWT created humans on earth as sosial beings to interact or communicate with each other (correspondence / collaboration). And along with the exponential development of information and communication technology, it has changed the mindset and attitude and the way of communicating in the virtual world of sosial networking pages via cyberspace. With the aim of gaining comfort, sharing ideas, calm, creative and innovative collaborations that are constructive in correspondence or user-generated content. In computer security, there are several important aspects of Confidentiality, so that the data on the device does not fall into unauthorized "hands" and which is not authorized. In general, the concept of cryptography is an information security or protection technique that is carried out by processing original information with a certain key using an encryption algorithm so as to produce new information that cannot be read directly. And to restore the integrity of the ciphertext, it can be returned to the original information through the description process. In principle, encryption is the process of randomizing or changing the initial message into other forms and structures so that the initial message cannot be recognized by other parties.Â Keywords: human, sosial-media, cryptography, cyberspace, encryption / decryption